2022
DOI: 10.3390/aquacj2010003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water Quality on Aquaculture Productivity in Ibanda District, Uganda

Abstract: Water quality plays a substantial role in maximizing fish productivity. Despite the efforts made by government to improve fish production, there are general complaints about the small size of fish produced in aquaculture systems. This study was conducted in order to assess the effect of water quality on aquaculture productivity in Ibanda District, Uganda. The specific objectives were to examine the status of water quality parameters (temperature, turbidity, pH, alkalinity, Ammonia content, hardness, Carbon dio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 2 publications
2
9
0
1
Order By: Relevance
“…From the four groups designed for acclimatization investigation, group 4 showed the highest survivability rate (83%) where stream water was used, indicating the more adequate water type for rearing the marble goby fish in laboratory conditions (Figure 5). These results were consistent with the other studies that suggested acclimatization of wildcaptured fish species through environments that have similar characteristics resembling their wild environments increase their survivability compared to direct exposure to a new environment due to stress (Marchesan et al, 2009;Tumwesigye et al, 2022). The survivability rate in the remaining three groups was less promising for achieving a more productive output.…”
Section: Discussionsupporting
confidence: 92%
“…From the four groups designed for acclimatization investigation, group 4 showed the highest survivability rate (83%) where stream water was used, indicating the more adequate water type for rearing the marble goby fish in laboratory conditions (Figure 5). These results were consistent with the other studies that suggested acclimatization of wildcaptured fish species through environments that have similar characteristics resembling their wild environments increase their survivability compared to direct exposure to a new environment due to stress (Marchesan et al, 2009;Tumwesigye et al, 2022). The survivability rate in the remaining three groups was less promising for achieving a more productive output.…”
Section: Discussionsupporting
confidence: 92%
“…The unfavourable pH values in aquaculture ponds result in a decline in the growth of cultured biota [Tumwesigye et al, 2022]. Lower pH values can limit the degradation of organic matter and allow it to accumulate in pond soil, leading to a high oxygen demand at the intersection of the bottom soil and pond water [Boyd, 2017;Hasibuan et al, 2021].…”
Section: Water Quality Characteristicsmentioning
confidence: 99%
“…Budidaya ikan hias saat ini mulai berkembang pesat dalam membantu meningkatkan nilai ekonomi dan rekreasi pertanian (1). Budidaya perikanan atau aquakulture adalah budidaya organisme akuatik termasuk ikan, moluska, krustasea, dan tanaman air [2]. Dalam budidaya ikan hias air tawar saat ini, yang banyak diminati masyarakat adalah Arwana (Scleropages formosus), Guppy (Poecilia reticulata), Koi (Cyprinus carpio), Betta (cupang), dan Rainbow (Melanonotaenia sp.…”
Section: Pendahuluanunclassified